Hydroxychloroquine and Mortality in SARS-Cov-2 Infection; the HOPECovid- 19 Registry - Núñez-Gil, Iván J.; Ayerbe, Luis; Fernandez-Pérez, Cristina; Estrada, Vicente; Eid, Charbel M.; Arroyo-Espliguero, Ramón; Romero, Rodolfo; Becerra-Muñoz, Víctor Manuel; Uribarri, Aitor; Feltes, Gisela; Trabattoni, Daniela; Molina, María; et al. (Anti-Infective Agents, 2023)
Background: Hydroxychloroquine (HCQ) may be an effective, safe, and affordable treatment for Covid-19 that can be used in selected patients. However, more evidence on its association when it is used in different stages of the disease with clinical outcomes is required. This observational study investigates the association between treatment with HCQ and mortality in patients with Covid-19. Methods: The data from 6217 patients who died or were discharged from 24 Spanish hospitals were analyzed. Propensity matching scores (PMS) were used. Results: 5094 patients received HCQ. Death was recorded for 17.5% of those who had HCQ and 34.1% of those who did not have it. Mortality was lower for those who had HCQ, OR=0.41 (95% CI=0.34-0.48). The PMS analysis also showed that mortality was lower for those receiving HCQ, OR=0.47 (95%CI=0.36-0.62). PMS analysis for categories revealed an association between HCQ and lowered mortality for patients over 65 years of age, with a past medical history of hypertension, for those who were diagnosed during admission with sepsis related organ failure or pneumonia, and for those with lymphocytopenia, raised troponin, LDH, ferritin and D-dimer. No increase in mortality associated with HCQ was observed in any category of any of the variables investigated. Conclusion: HCQ could be associated with lower mortality for older patients, those with more severe disease and raised inflammatory markers. Further RCTs, observational studies, and summaries of both types of evidence on this topic are necessary to select the precise profile of patients that may benefit from HCQ.
Keywords: SARS-Cov-2